Stable Knockdown of Genes Encoding Extracellular Matrix Proteins in the C2C12 Myoblast Cell Line Using Small-Hairpin (sh)RNA - Taye, Nandaraj (J Vis Exp, 2020)
Extracellular matrix (ECM) proteins are crucial for skeletal muscle development and homeostasis. The stable knockdown of genes coding for ECM proteins in C2C12 myoblasts can be applied to study the role of these proteins in skeletal muscle development. Here, we describe a protocol to deplete the ECM protein ADAMTSL2 as an example, using small-hairpin (sh) RNA in C2C12 cells. Following transfection of shRNA plasmids, stable cells were batch-selected using puromycin. We further describe the maintenance of these cell lines and the phenotypic analysis via mRNA expression, protein expression, and C2C12 differentiation. The advantages of the method are the relatively fast generation of stable C2C12 knockdown cells and the reliable differentiation of C2C12 cells into multinucleated myotubes upon depletion of serum in the cell culture medium. Differentiation of C2C12 cells can be monitored by bright field microscopy and by measuring the expression levels of canonical marker genes, such as MyoD, myogenin, or myosin heavy chain (MyHC) indicating the progression of C2C12 myoblast differentiation into myotubes. In contrast to the transient knockdown of genes with small-interfering (si) RNA, genes that are expressed later during C2C12 differentiation or during myotube maturation can be targeted more efficiently by generating C2C12 cells that stably express shRNA. Limitations of the method are a variability in the knockdown efficiencies, depending on the specific shRNA that may be overcome by using gene knockout strategies based on CRISPR/Cas9, as well as potential off-target effects of the shRNA that should be considered.